2019
DOI: 10.1136/bmjopen-2018-026854
|View full text |Cite|
|
Sign up to set email alerts
|

Dose–response association between physical activity and non-alcoholic fatty liver disease: a case–control study in a Chinese population

Abstract: AimPhysical activity plays an important role in the development of non-alcoholic fatty liver disease (NAFLD).However, the optimal intensity and dose of physical activity for the treatment of NAFLD have yet to be found. In the present study, we aimed to provide a dose–response association between physical activity and NAFLD in a Chinese population.MethodsWe recruited 543 patients with NAFLD diagnosed by abdominal ultrasonography, and 543 age-matched and sex-matched controls. The amount of physical activity, sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 41 publications
(31 reference statements)
1
17
0
Order By: Relevance
“…Further increases in physical activity (1000 MET-minutes/week) were associated with a 33% risk reduction in NAFLD (RR = 0.67, 95% CI 0.54-0.83). These findings are consistent with those of Li and colleagues who reported that moderate-and vigorous-intensity physical activity effectively reduced the risk of NAFLD independent of energy intake and sedentary time (>684 MET-minutes/week compared to none: OR 0.58, 95% CI 0.40 to 0.86, vigorous-intensity physical activity: >960 MET-min/week compared to none: OR 0.63, 95% CI 0.41 to 0.95) [39]. Li et al used ultrasound measurements to assess LF.…”
Section: Exercise and Liver Fatsupporting
confidence: 89%
See 1 more Smart Citation
“…Further increases in physical activity (1000 MET-minutes/week) were associated with a 33% risk reduction in NAFLD (RR = 0.67, 95% CI 0.54-0.83). These findings are consistent with those of Li and colleagues who reported that moderate-and vigorous-intensity physical activity effectively reduced the risk of NAFLD independent of energy intake and sedentary time (>684 MET-minutes/week compared to none: OR 0.58, 95% CI 0.40 to 0.86, vigorous-intensity physical activity: >960 MET-min/week compared to none: OR 0.63, 95% CI 0.41 to 0.95) [39]. Li et al used ultrasound measurements to assess LF.…”
Section: Exercise and Liver Fatsupporting
confidence: 89%
“…Hallworth and colleagues randomized participants to 12 weeks of HITT on a cycle ergometer three times a week. Participants were instructed to perform 5 intervals of cycling at 16-17 on the Borg scale for 3 min followed by 3 min of recovery [39]. Abdelbasset et al randomized participants to an eight-week cycling protocol.…”
Section: Exercise and Liver Fatmentioning
confidence: 99%
“… 17 This dose-dependent negative association of physical activity with CLD in our study is also consistent with data reporting a dose-response association between physical activity and NAFLD. 18 Based on our data, an additional walk of 40 min per day ( e.g. change from quartile 1 to quartile 2) could decrease the risk of liver disease development by 22%.…”
Section: Discussionmentioning
confidence: 70%
“…31 Another case-control study found that among men physical activity was inversely associated with the risk of NAFLD in a dose-dependent manner. 32 A review emphasized the independent effect of physical activity, including aerobic exercise in the treatment of NAFLD. 33 Exercise increases fatty acid oxidation, decreases fatty acid synthesis, and prevents mitochondrial and hepatocellular damage.…”
Section: Discussionmentioning
confidence: 99%